Prepare special exercises Palmquaomat rubber and its impact on the development of the movement of the feet defensive basketball speed - Hussain Alaa Al-Taee ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The research aims to prepare rubber Palmquaomat special exercises for the development of the movement of the feet defensive basketball speed. As well as to identify the effect of exercise for the development of the movement of the feet defensive basketball speed. The identified research sample players young students Sports Club and hired a researcher some tests, and tools and equipment assistance to help him in the completion of the search, and adopted researcher prepared by the coach, and through this approach, the researcher introduction of the proposed approach within the practical side in the module. The proposed training curriculum included special exercises took (8) weeks, starting from 13/03/2016 until 12/05/2016, and by (3) training units per week, and that the most important conclusions reached by the researcher are: the emergence of significant differences in the post tests to test the movement defensive feet. The most important thing recommended by the researcher is the use of special exercises that use showed positive results and the use of methods and new ways of training to develop the game.